On Bayesian estimation from two parameter Bathtub-Shaped lifetime distribution based on progressive first-failure-censored sampling - Javadkhani, Nooshin; Azhdari, Parvin; Azimi, Reza (International Journal of Scientific World, 2014)
This paper presents different methods of Bayesian estimation like empirical Baysian estimation, Expectation of Bayesian estimation to estimate parameter and reliability function of two parameter bathtub-shaped lifetime distribution based on progressively firrst-failure-censored samples under minimum expected and LINEX loss functions. Comparisons among estimators are investigated through simulation study.Keywords: Progressive rst-failure-censoring scheme, Empirical Bayesian Estimation, E-Bayesian Estimation, Bathtub-Shaped lifetime distribution .